Phase angle is associated with advanced fibrosis in patients chronically infected with hepatitis C virus - Dorna, Mariana De Souza [UNESP] (2016)
Aims The objective of this study was to evaluate the association of phase angle (PhA) with advanced liver fibrosis in patients chronically infected with hepatitis C virus (HCV). Main methods One hundred sixty consecutive patients chronically infected with HCV were treated at the Hepatitis C outpatient care setting of our hospital from April 2010 to May 2011 and prospectively evaluated. Bioelectrical impedance analysis measurements were performed during the first hospital visit. Biochemical measurements and liver biopsy data were collected from the patients' medical records and included in the analysis only if they were performed within three months of the inclusion of the patient in the study. Key findings One hundred sixty consecutive patients were evaluated and 25 patients were excluded. A total of 135 patients with 49.8 ± 11.4 years old were studied. Among these patients, 60% were male and the PhA was 6.5 ± 0.8°. Regarding the stage of fibrosis, patients with advanced fibrosis were older and had more insulin resistance and more inflammation compared with patients that had mild fibrosis. Logistic regression analysis revealed that PhA was a predictor of advanced fibrosis even when adjusted for gender, age, HOMA-IR, HDL-cholesterol and AST (OR: 0.227; CI 95%: 0.090-0.569; p: 0.013). The best PhA cut-off points associated with advanced fibrosis for the combined data, for females and for males were 6.43°, 5.94° and 6.72°, respectively. Significance PhA was predictor of advanced liver fibrosis in patients chronically infected with HCV. In the sample evaluated, for each one-degree decrease in PhA, the risk of advanced fibrosis increased more than four-fold.